2022
DOI: 10.1093/lambio/ovac006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus spp. cell-free supernatant against planktonic growth and biofilm formation of foodborne Escherichia coli isolates

Abstract: The aim of this work was to evaluate the anti-Escherichia coli effect of cell-free supernatant (CFS) of Lactobacillus spp. against planktonic and biofilm forms of foodborne isolates. Escherichiacoli strains (P12, P25, P35 and P36), previously isolated from fresh filets of fish, were subjected to antimicrobial susceptibility determination by the disc-diffusion agar method. Subsequently, the antagonistic effect between probiotic and pathogenic strains was determined by spot overlay assay. Finally, the CFS activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Structural analysis of the biofilms through phase contrast microscopy imaging provided evidence of the ability of the components released in the CSF of L. casei IMAU60214 to inhibit the architectural development of biofilms formed by the DEC strains. It was also observed that the CSF from L. casei IMAU60214 exhibits a protective effect on HT-29 epithelial cells infected with the EAEC and EHEC strains, producing toxins such as Pet toxin and Shiga-like toxin (SLT), respectively [ 58 , 59 , 60 , 61 , 62 ]. In this regard, Navarro et al [ 63 ] showed that Pet secreted by strains of the EAEC pathotype induces morphological changes in the mucosa characterized by flattening of the intestinal villi with cell damage to the intestinal mucosa evaluated in an experimental rat ligated loop model.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis of the biofilms through phase contrast microscopy imaging provided evidence of the ability of the components released in the CSF of L. casei IMAU60214 to inhibit the architectural development of biofilms formed by the DEC strains. It was also observed that the CSF from L. casei IMAU60214 exhibits a protective effect on HT-29 epithelial cells infected with the EAEC and EHEC strains, producing toxins such as Pet toxin and Shiga-like toxin (SLT), respectively [ 58 , 59 , 60 , 61 , 62 ]. In this regard, Navarro et al [ 63 ] showed that Pet secreted by strains of the EAEC pathotype induces morphological changes in the mucosa characterized by flattening of the intestinal villi with cell damage to the intestinal mucosa evaluated in an experimental rat ligated loop model.…”
Section: Discussionmentioning
confidence: 99%